2013
DOI: 10.4018/ijicte.2013100107
|View full text |Cite
|
Sign up to set email alerts
|

A Procedure to Create a Pedagogic Conversational Agent in Secondary Physics and Chemistry Education

Abstract: Pedagogic Conversational Agents are computer applications that can interact with students in natural language. They have been used with satisfactory results on the instruction of several domains. The authors believe that they could also be useful for the instruction of Secondary Physics and Chemistry Education. Therefore, in this paper, the authors present a procedure to create an agent for that domain. First, teachers have to introduce the exercises with their correct answers. Secondly, students will be prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…The subjects of the dialogues or the topics that educational agents focus on them can be various, such as mathematics ( Melis and Siekmann, 2004 ; Sabo et al, 2013 ; Aguiar et al, 2014 ; Zhang and Jia, 2017 ), physics ( VanLehn et al, 2002 ; Pérez-Marín and Boza, 2013 ), medicine ( Frize and Frasson, 2000 ; Suebnukarn and Peter, 2004 ; Martin et al, 2009 ), computer science ( Wallace, 1995 ; Weerasinghe and Mitrovic, 2011 ; Koedinger et al, 2013 ; Wang et al, 2015 ). In these examples, conversational agents are used to support learning about a particular subject, and the key element in all these agents is their domain knowledge (implemented by different means).…”
Section: Background Knowledge and Related Workmentioning
confidence: 99%
“…The subjects of the dialogues or the topics that educational agents focus on them can be various, such as mathematics ( Melis and Siekmann, 2004 ; Sabo et al, 2013 ; Aguiar et al, 2014 ; Zhang and Jia, 2017 ), physics ( VanLehn et al, 2002 ; Pérez-Marín and Boza, 2013 ), medicine ( Frize and Frasson, 2000 ; Suebnukarn and Peter, 2004 ; Martin et al, 2009 ), computer science ( Wallace, 1995 ; Weerasinghe and Mitrovic, 2011 ; Koedinger et al, 2013 ; Wang et al, 2015 ). In these examples, conversational agents are used to support learning about a particular subject, and the key element in all these agents is their domain knowledge (implemented by different means).…”
Section: Background Knowledge and Related Workmentioning
confidence: 99%
“…For instance, using Autotutor (Graesser et al 2008), it has been found out that mixed-dialogue interaction, in which both the agent and the student can change the turn of the conversation, can improve the score of the student up to one point; the adaptive intelligent tutorial dialogue module in the BEETLE II (Dzikovska et al 2011) pedagogic agent system provided significant learning gains for students interacting with the system; and, Mike (Lane et al 2011) behaves differently depending on the students' feelings and some pedagogic choices with good results. Some agents that have been used in different domains are the following: Herman the Bug (Lester et al 1997), Steve (Rickel and Johnson, 1999), Guilly (Nunes et al 2002), Sam (Ryokai et al 2003), Baldi (Massaro et al 2005), Betty (Biswas et al 2009;Segedy et al 2013), Agents in Active Worlds (Holmes, 2007), SBEL agents (Reategui et al 2007), MyPet (Chen et al 2009), Fisca (Pérez-Marín andBoza, 2013), Pascall (Da Costa Pinho et al 2013), MentorChat (Tegos et al 2014), and Metabots (Griol et al 2014).…”
Section: Related Workmentioning
confidence: 99%